ANALISIS KURIKULUM MANDIRI DI SEKOLAH ANAK BERKEBUTUHAN KHUSUS HARAPAN BANGKIT MULYA: STUDI KUALITATIF MELALUI WAWANCARA DAN OBSERVASI - Kurnia, Ira Restu; Laelly, Tazkia Aisha; Febriyanti, Utari; Noviyanti, Noviyanti; Apriliani, Firda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
A self-contained curriculum provides flexibility in planning, implementing and evaluating learning that focuses on developing students' life skills, academic and social-emotional abilities. This study aims to analyze the implementation of a self-contained curriculum at Harapan Bangkit Mulya School for Children with Special Needs, designed to meet the unique needs of students with disabilities. Using a descriptive qualitative approach, data was collected through in-depth interviews, observation and documentation, involving the principal, teachers and staff as research subjects. The results show that this curriculum is effective in creating inclusive learning that is relevant to students' needs. The practical and contextual approach becomes the main method in implementing learning, allowing students to learn through real experiences. The advantages of this curriculum include flexibility and focus on students' individual needs. However, there are challenges such as limited facilities, lack of teacher training, and lack of parental involvement.